Responsibility Without Freedom? Folk Judgements About Deliberate Actions - Vierkant, Tillmann; Deutschländer, Robert; Sinnott-Armstrong, Walter; Haynes, John-Dylan (Frontiers in Psychology, 2019)
A long-standing position in philosophy, law, and theology is that a person can be held morally responsible for an action only if they had the freedom to choose and to act otherwise. Thus, many philosophers consider freedom to be a necessary condition for moral responsibility. However, empirical findings suggest that this assumption might not be in line with common sense thinking. For example, in a recent study we used surveys to show that – counter to positions held by many philosophers – lay people consider actions to be free when they are spontaneous rather than being based on reasons. In contrast, responsibility is often considered to require that someone has thought about the alternative options. In this study we use an online survey to directly test to which degree lay judgements of freedom and responsibility match. Specifically, we test whether manipulations of deliberation affect freedom and responsibility judgements in the same way. Furthermore, we also test the dependency of these judgements on a person’s belief that their decision had consequences for their personal life. We find that people are generally considered to be more responsible for their actions than they are considered free, across most of the conditions tested. Furthermore, we found that deliberation had an opposite effect on freedom and responsibility judgements. People were considered more free when they acted spontaneously, whereas they were considered more responsible when they deliberated about their actions. These results seem to suggest that deliberating about reasons is crucially important for the lay concept of responsibility, while it is not obviously crucial for the lay notion of freedom. One way of interpreting our findings for the interdisciplinary debate on free will and responsibility could be to suggest that lay beliefs match the philosophical position of semi-compatibilism. Semi compatibilists insist that the metaphysical debate on the nature of free will can be separated from the debate on conditions of responsible agency. Our findings seem to suggest that the lay people are intuitive semi-compatibilists.